Assessment of cost of innovation versus the value of health gains associated with treatment of chronic hepatitis C in the United States: The quality-adjusted cost of care. Issue 41 (October 2016) - Younossi, Zobair M.; Park, Haesuk; Dieterich, Douglas; Saab, Sammy; Ahmed, Aijaz; Gordon, Stuart C.
Abstract: Background: New direct-acting antiviral (DAA) therapy has dramatically increased cure rates for patients infected with hepatitis C virus (HCV), but has also substantially raised treatment costs. Aim: The aim of this analysis was to evaluate the therapeutic benefit and net costs (i.e. efficiency frontier) and the quality-adjusted cost of care associated with the evolution of treatment regimens for patients with HCV genotype 1 in the United States. Design: A decision-analytic Markov model. Data source: Published literature and clinical trial data. Time horizon: Life Time. Perspective: Third-party payer. Intervention: This study compared four approved regimens in treatment-naïve genotype 1 chronic hepatitis C patients, including pegylated interferon and ribavirin (PR), first generation triple therapy (boceprevir + PR and telaprevir + PR), second generation triple therapy (sofosbuvir + PR and simeprevir + PR) and all-oral DAA regimens (ledipasvir/sofosbuvir and ombitasvir + paritaprevir/ritonavir + dasabuvir ± ribavirin). Outcome measure: Quality-adjusted cost of care (QACC). QACC was defined as the increase in treatment cost minus the increase in the patient's quality-adjusted life years (QALYs) when valued at 50, 000 per QALY. Results: All-oral therapy improved the average sustained virologic response (SVR) rate to 96%, thereby offsetting the high drug acquisition cost of 85, 714, which resulted in the highest benefit based on the efficiency frontier. Furthermore, while oral therapies increased HCV drug costs by 48, 350, associated QALY gains decreased quality-adjusted cost of care by 14, 120 compared to dual therapy. When the value of a QALY was varied from 100, 000 to 300, 000, the quality adjusted cost of care compared to dual therapy ranged from − 21, 234 to − 107, 861, − 89, 007 to − 293, 130, − 176, 280 to − 500, 599 for first generation triple, second generation triple, and all-oral therapies, respectively. Primary efficacy and safety measurements for drug regimens were sourced from clinical trials data rather than a real-world setting. Factors such as individual demographic characteristics, comorbidities and alcohol consumption of the individual patients treated may alter disease progression but were not captured in this analysis. Conclusion: New DAA treatments provide short-term and long-term clinical and economic value to society. Primary funding source: Gilead Sciences, Inc. Abstract : Supplemental Digital Content is available in the text